Echinostoma revolutum: Freshwater snails as the second intermediate hosts in Chiang mai, Thailand - Kittichai Chantima (2018)
The occurrence of 37-collar spined echinostome metacercariae in freshwater snails was investigated in 6 districts of Chiang Mai Province, Thailand, from October 2011 to April 2012. A total of 2,914 snails that belong to 12 species were examined, and 7 snail species (Clea helena, Eyriesia eyriesi, Bithynia funiculata, Bithynia siamensis siamensis, Filopaludina doliaris, Filopaludina sumatrensis polygramma, and Filopaludina martensi martensi) were found infected with echinostome metacercariae. The prevalence of metacercariae was the highest in Filopaludina spp. (38.5-58.7%) followed by B. funiculata (44.0%), E. eyriesi (12.5%), B. siamensis siamensis (8.2%), and C. helena (5.1%). Metacercariae were experimentally fed to hamsters and domestic chicks, and adult flukes were recovered from both hosts at days 15 and 20 post-infection. The adult flukes were identified based on morphological features, morphometrics, host-parasite relationships, and geographical distribution. They were compatible to Echinostoma revolutum or Echinostoma jurini, with only minor differences. As the adults were recovered from both hamsters and chicks, our specimens were more compatible to E. revolutum rather than E. jurini (reported only from mammals). This is the first report for metacercariae of E. revolutum in the snail host, C. helena, and also confirmed that Filopaludina spp., E. eryresi, and Bithynia spp. act as the second intermediate hosts of E. revolutum under natural conditions, which are indigenously distributed in Chiang Mai province. © 2013, Korean Society for Parasitology and Tropical Medicine.